Pengaruh Kepemimpinan Transformasional dan Inovasi Terhadap Orientasi Kewirausahaan dan Kinerja Koperasi di Kota Surabaya - Anjarwati, Tri (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2017)
This study aims to prove and analyze the influence of Transformational Leadership and Innovation to the Orientation of Entrepreneurship and Cooperative Performance in Surabaya City. The population in this study were all primary cooperatives in Surabaya city which amounted to 219 cooperatives with criteria: (a) Has minimum membership of 100 people, (b) Active and operates RAT 3 consecutive years, (c) Owns more than two units business, (d) Having assets above 1 Billion. The sample in this research is 142 cooperatives. The data used in this study is the primary data sourced from the questionnaire. Data analysis and hypothesis test in this research using Structural Equation Model (SEM). The results showed that the variables of Transformational Leadership and Innovation have a significant effect on the Orientation of Entrepreneurship. Transformational and Innovation Leadership Variables have no significant effect on Cooperative Performance in Surabaya City. Orientation of Entrepreneurship has a significant effect on Cooperative Performance in Surabaya City.